Entfremdung und fundamentalistische Identitätskonstruktion im zeitgenössischen Indien - Horstmann, Monika (Internationales Asien-Forum, 1994)
In the process of modernization the identity of Indian society has been challenged forcefully. One way of responding to this challenge lies in the ideology of Hindutva („Hindudom“) which represents a nationalistic recasting of Hinduism and is alleged by its spokesmen to be pristine unalloyed Hinduism restored. It claims to provide a modern Hindu identity. Its propounders furthermore claim Hindus, whose status is religiously legitimized, as the cultural and racial majority of India. „Hindudom“ is therefore prone to take a totalitarian stance towards secularism and minority groups. It is backed institutionally above all by three related organisations which play a major role in the political arena, namely the RSS, VHP and BJP. The paper presents a discussion of the programmatic inaugural speech delivered in April 1994 by the then newly elected president of the RSS. It underscores characteristics of the ideology that have been delineated in the introductory part of the paper.